Media and culture of peace for democratic coexistence (Revista de Investigaciones Universidad del Quindío, 2021)
The development of societies within an established order considers a culture based on the norms and competent obligations to the citizen, social structures and institutions of the justice system. In this sense, empowering the communication media to ensure a society with a culture of peace reflected in a democratic coexistence, involves various actors with a goal of common good, which directly and indirectly benefits other sectors or areas of the population and institutions. This document aims to give an overview of how beneficial it is to socialize, interact and innovate action mechanisms that prevail in a sustainable, democratic and integral society, based on participation, plurality, tolerance and respect, with the aim of reflecting on the importance of the implementation of the culture of peace as a mechanism that allows to favor and promote civic and social values, in the construction of an effective democratic coexistence and therefore the prevention of violence, including politics, and the important role of the media , as a body for the processing of timely information to citizens, which often go beyond the intention of informing, to influence sympathies or spirits, "contrary sensu", confronting political actors and their supporters.
Keywords: inclusive coexistence; State; education; peace; civil society